2016
DOI: 10.1093/toxsci/kfw259
|View full text |Cite
|
Sign up to set email alerts
|

BDE-47 and BDE-49 Inhibit Axonal Growth in Primary Rat Hippocampal Neuron-Glia Co-Cultures via Ryanodine Receptor-Dependent Mechanisms

Abstract: Title we quantified the effects of individual BDE congeners on not only dendritic but also axonal 36 growth since both are regulated by RyR-dependent mechanisms, and both are critical 37 determinants of neuronal connectivity. Primary neuronal-glial co-cultures dissociated from the 38 neonatal rat hippocampus were exposed to BDE-47 or BDE-49 in the culture medium at 39 concentrations ranging from 20 pM to 2 µM. At these concentrations, neither PBDE congener 40 altered dendritic arborization. In contrast, at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…Cells were fixed with 4% paraformaldehyde for 20 min on DIV 9 and immunostained as described (Chen et al, 2017a). Briefly, after fixation, cells were washed with phosphate buffered saline (PBS; 3.6 mM disodium phosphate, 1.4 mM monosodium phosphate, 150 mM sodium chloride, pH 7.2) and permeabilized with 0.1% Triton X-100 (Sigma-Aldrich) in PBS for 5 min, incubated in blocking buffer containing 10% bovine serum albumin (Sigma-Aldrich) and 5% goat serum (Vector Laboratories, Burlingame, California) in PBS for 1 h and coincubated overnight at 4 C with antibodies targeting MAP2B (1:1000, AB5622, Millipore, Burlington, Massachusetts) to label neurons and glial fibrillary acidic protein (GFAP, 1:1000, no.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Cells were fixed with 4% paraformaldehyde for 20 min on DIV 9 and immunostained as described (Chen et al, 2017a). Briefly, after fixation, cells were washed with phosphate buffered saline (PBS; 3.6 mM disodium phosphate, 1.4 mM monosodium phosphate, 150 mM sodium chloride, pH 7.2) and permeabilized with 0.1% Triton X-100 (Sigma-Aldrich) in PBS for 5 min, incubated in blocking buffer containing 10% bovine serum albumin (Sigma-Aldrich) and 5% goat serum (Vector Laboratories, Burlingame, California) in PBS for 1 h and coincubated overnight at 4 C with antibodies targeting MAP2B (1:1000, AB5622, Millipore, Burlington, Massachusetts) to label neurons and glial fibrillary acidic protein (GFAP, 1:1000, no.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…All these findings argue against a single mechanism of action underlying the developmental neurotoxicity of brominated or organophosphate flame retardants, e.g. thyroid disruption or actions at ryanodine receptors (Chen et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the neurotoxic activities of NDL PCBs, PBDEs and their hydroxylated metabolites are additive, and that a dose addition model for estimating risk may be appropriate [34,71]. However, unlike NDL PCBs, which selectively alter dendritic complexity, neuronal-glial co-cultures from rat hippocampus exposed to BDE-47 or BDE-49 exhibited delayed neuronal polarization resulting in significant inhibition of axonal outgrowth during 1 3 the first few days in vitro, but no later influences on dendritic complexity [24]. Interestingly, the axon inhibitory effects of these PBDEs were blocked by pharmacological antagonism of RyR or siRNA knockdown of RyR2, indicating common molecular mechanisms affecting two distinct developmental processes of neuronal connectivity.…”
Section: Are Pcbs the Tip Of The Ndl-pop Iceberg?mentioning
confidence: 99%